Highly functionalized alkenes produced from base-free organocatalytic Wittig reactions: (E)-3-benzylidenepyrrolidine-2,5-dione, (E)-3-benzylidene-1-methylpyrrolidine-2,5-dione and (E)-3-benzylidene-1-tert-butylpyrrolidine-2,5-dione - Schirmer, Marie-Luis; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section C Structural Chemistry)
The Wittig reaction is a fundamental transformation for the preparation of alkenes from carbonyl compounds and phosphonium ylides. The ylides are prepared prior to the olefination step from the respective phosphonium salts by deprotonation utilizing strong bases. A first free-base catalytic Wittig reaction for the preparation of highly functionalized alkenes was based on tributylphosphane as the catalyst. Subsequently we developed a system employing a phospholene oxide as a pre-catalyst and trimethoxysilane as reducing agent which operates under milder conditions. The title compounds, ( E )-3-benzylidenepyrrolidine-2,5-dione, C 11 H 9 NO 2 , (I), the methylpyrrolidine derivative, C 12 H 11 NO 2 , (II), and the tert- butylpyrrolidine derivative, C 15 H 17 NO 2 , (III), have been synthesized by base-free catalytic Wittig reactions. In the crystal of (I), molecules are linked into centrosymmetric dimers via pairs of N—H...O hydrogen bonds. Furthermore, in the crystal structure of (III), there are two molecules in the asymmetric unit, whereas in (I) and (II), only one molecule is present.
Keywords: T2

Atom economical synthesis of di- and trithiocarbonates by the lithium tert-butoxide catalyzed addition of carbon disulfide to epoxides and thiiranes - Diebler, J.; Spannenberg, A.; Werner, Thomas (Organic and Biomolecular Chemistry)
The lithium tert-butoxide catalyzed addition of CS2 to epoxides and thiiranes under mild conditions is reported. A mechanism has been proposed taking into account the regio- and stereochemical outcome of the reaction.
Keywords: CSSD

A novel zinc based binary catalytic system for CO2utilization under mild conditions - Desens, Willi; Kohrt, Christina; Spannenberg, Anke; Werner, Thomas (Organic Chemistry Frontiers)
A novel zinc based binary catalytic system for the synthesis of cyclic carbonates under mild and solvent-free conditions utilizing CO2as a C1 building block is reported.
Keywords: T1; T3; CSSD

Alkoxide-Initiated Regioselective Coupling of Carbon Disulfide and Terminal Epoxides for the Synthesis of Strongly Alternating Copolymers - Diebler, Johannes; Komber, Hartmut; Häußler, Liane; Lederer, Albena; Werner, Thomas (Macromolecules)
Keywords: CSSD

Iron-Based Binary Catalytic System for the Valorization of CO2 into Biobased Cyclic Carbonates - Büttner, Hendrik; Grimmer, Christoph; Steinbauer, Johannes; Werner, Thomas (ACS Sustainable Chemistry & Engineering)
Keywords: T1; T3; CSSD

Novel Base-Free Catalytic Wittig Reaction for the Synthesis of Highly Functionalized Alkenes - Schirmer, Marie-Luis; Adomeit, Sven; Spannenberg, Anke; Werner, Thomas (Chemistry - A European Journal)
Keywords: T2; CSSD

Regio- and Stereoselective Synthesis of Dithiocarbonates under Ambient and Solvent-Free Conditions - Diebler, Johannes; Spannenberg, Anke; Werner, Thomas (ChemCatChem)
Keywords: CSSD

Convergent Activation Concept for CO2Fixation in Carbonates - Desens, Willi; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: T1; CSSD

Phospholane-Catalyzed Wittig Reaction - Werner, Thomas; Hoffmann, Marcel; Deshmukh, Sunetra (European Journal of Organic Chemistry)
Keywords: T2; CSSD

Crystal structure of diethyl (E)-2-[(benzofuran-2-yl)methylidene]succinate - Schirmer, Marie-Luis; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section E Crystallographic Communications)
The title compound, C 17 H 18 O 5 , was synthesized by a base-free catalytic Wittig reaction. The molecule consists of a diethyl itaconate unit, which is connected via the C=C double bond to a benzofuran moiety. The benzofuran ring system (r.m.s. deviation = 0.007 Å) forms dihedral angles of 79.58 (4) and 12.12 (10)° with the mean planes through the cis and trans ethoxycarbonyl groups, respectively. An intramolecular C—H...O hydrogen bond involving the O atom of the benzofuran moiety is observed. In the crystal, molecules are linked into ribbons running parallel to the b axis by C—H...O hydrogen bonds.
Keywords: T2

Scope and Limitation of the Microwave-Assisted Catalytic Wittig Reaction - Hoffmann, Marcel; Deshmukh, Sunetra; Werner, Thomas (European Journal of Organic Chemistry)
Keywords: T2; CSSD

Recycling of Phosphorus-Based Organocatalysts by Organic Solvent Nanofiltration - Großeheilmann, Julia; Büttner, Hendrik; Kohrt, Christina; Kragl, Udo; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: T1; T2; CSSD

Synthesis of Cyclic Carbonates from Epoxides and Carbon Dioxide by Using Bifunctional One-Component Phosphorus-Based Organocatalysts - Büttner, Hendrik; Steinbauer, Johannes; Werner, Thomas (ChemSusChem)
Keywords: T1; T2; CSSD

Recyclable Bifunctional Polystyrene and Silica Gel-Supported Organocatalyst for the Coupling of CO2with Epoxides - Kohrt, Christina; Werner, Thomas (ChemSusChem)
Keywords: T1; T2; CSSD

Highly Efficient Polymer-Supported Catalytic System for the Valorization of Carbon Dioxide - Desens, Willi; Kohrt, Christina; Frank, Marcus; Werner, Thomas (ChemSusChem)
Keywords: T1; T2; CSSD

First Base-Free Catalytic Wittig Reaction - Schirmer, Marie-Luis; Adomeit, Sven; Werner, Thomas (Organic Letters)
Keywords: T2; CSSD

Bifunctional One-Component Catalysts for the Addition of Carbon Dioxide to Epoxides - Büttner, Hendrik; Lau, Kornelia; Spannenberg, Anke; Werner, Thomas (ChemCatChem)
Keywords: T1; CSSD

2-Hydroxyethylammonium iodide - Kohrt, Christina; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section E Structure Reports Online)
In the crystal structure of the title salt, C 2 H 8 NO + ·I − , N—H...O, N—H...I and O—H...I hydrogen bonds lead to the formation of layers staggered along the c axis.
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

A Catalytic System for the Activation of Diorganozinc Reagents - Werner, Thomas; Bauer, Matthias; Riahi, Abdol Majid; Schramm, Heiko (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

First Microwave-Assisted Catalytic Wittig Reaction - Werner, Thomas; Hoffmann, Marcel; Deshmukh, Sunetra (European Journal of Organic Chemistry)
Keywords: T2; CSSD